Buckling of cylindrical concrete tanks and silos due to prestressing — nonlinear approach. (July 2022) - Kawecki, Bartosz; Halicka, Anna; Podgórski, Jerzy
Abstract: The buckling of concrete cylindrical tanks and silos is associated mainly with prestressing, which influences the meridional critical force. Higher compression produces a lower meridional critical force. For three-dimensional structures subjected to biaxial or triaxial loading, the simplified methods of stability analysis proposed in Eurocode standard for concrete structures are inappropriate. The authors try to answer which procedure may be helpful for the assessment of buckling possibility, which results from prestressing of cylindrical structures. The numerical analyses are performed with the use of "Simulia Abaqus system", which allows the nonlinear stability analysis adopting the plasticity-based damage material model and assuming initial imperfections. Two variants of load distribution (constant and hydrostatic external prestress) and two variants of wall-foundation connection are considered. The results are presented with the use of two parameters. The first one constitutes the ratio of lateral pressure to vertical pressure on the upper edge. The second one describes the ratio of current vertical force – corresponding to real load – to the initial test value of the iterative process. The obtained relationships of critical vertical force and the level of external prestress for cylindrical tank of height twice the diameter can be the guideline for engineers in designing process. Highlights: The prestressing of concrete tanks and silos influences the critical value of vertical force applied onto upper edge of structure. Only the non-linear analysis may answer the question of the real stability performance of concrete cylindrical shells. The prestress distribution and the boundary conditions influence both the critical vertical force and the location of the stability loss. The influence of hoop prestress onto the vertical critical load may be assessed with use of the presented graphical relationships.